The role of Arabidopsis MYB2 in miR399f-mediated phosphate-starvation response - Baek, Dongwon (Landes Bioscience, 2013)
In plants, microRNA399 (miR399) is a major regulator of phosphate (Pi) homeostasis by way of post-transcriptional mechanisms including transcript cleavage and transcriptional repression. Although miRNA genomic organization, biogenesis, and mode of action in plants are known, the regulatory mechanisms affecting miRNAs are poorly understood. We have shown that AtMYB2 functions as a transcriptional activator for miR399f expression in the context of phosphate homeostasis. AtMYB2 directly binds to a MYB-binding site in the promoter of the miR399f precursor and regulates miR399f expression. In addition, AtMYB2 transcripts are induced under Pi deficiency. The overexpression of AtMYB2 affects root system architecture (RSA), indicated by suppression of primary root growth and enhanced development of root hairs. AtMYB2 and miR399f are expressed and localized in the same tissues under Pi limitation. This study establishes that AtMYB2 regulates Pi-starvation responses (PSR) by activating of miR399f transcript, suggesting that an analysis of this miRNA promoter could reveal the existence and extent of crosstalk with other signaling mechanisms.